Metric properties of the “timed get up and go- modified version” test, in risk assessment of falls in active women - Alfonso-Mora, Margareth Lorena (Colombia Medica, 2017)
Objective: To analyse the metric properties of the Timed Get up and Go - Modified Version Test (TGUGM), in risk assessment of falls in a group of physically active women. Methods: A sample was constituted by 202 women over 55 years of age, were assessed through a crosssectional study. The TGUGM was applied to assess their fall risk. The test was analysed by comparison of the qualitative and quantitative information and by factor analysis. The development of a logistic regression model explained the risk of falls according to the test components. Results: The TGUGM was useful for assessing the risk of falls in the studied group. The test revealed two factors: the Get Up and the Gait with dual task. Less than twelve points in the evaluation or runtimes higher than 35 seconds was associated with high risk of falling. More than 35 seconds in the test indicated a risk fall probability greater than 0.50. Also, scores less than 12 points were associated with a delay of 7 seconds more in the execution of the test (p= 0.0016). Conclusions: Factor analysis of TGUGM revealed two dimensions that can be independent predictors of risk of falling: The Get up that explains between 64% and 87% of the risk of falling, and the Gait with dual task, that explains between 77% and 95% of risk of falling.